Looking for Lincoln in Illinois : a guide to Lincoln's Eighth Judicial Circuit - Fraker, Guy C., 1938- (Southern Illinois University Press, 2017)
"This guidebook allows readers to drive (or just read about) the Eighth Judicial Circuit during Lincoln's era. It contains detailed directions, brief stories about Lincoln locations and events, and a significant collection of photographs, including images of all the court houses in which Lincoln practiced"--